Suleiman pasha al-Khadems campaign against Yemen and India 1538 - جبور علاء الدين (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research talks about an ottoman military campaign to yemen and india carried out by the governor of Egypt Suleiman pasha al-Khadem in 1538, commissioned by the ottoman Sultan Suleiman the Magnificent, to extend the borders of ottoman control The subjection of Yemen to the ottoman rule due to the weakness of the Mamluk power in yemen, which was quick to recognize the ottoman sovereignty, and the protection of Islamic holy sites in the Arab seas. The ottomans realized after seizing Egypt the importance of yemens role in their conflict. With the Portuguese, and his assistant, the sultans and princes of india in resisting the colonial expansion of the Portuguese on the coasts of the Red sea, and discusses its details from the causes of events and results, as well as sheds light on its importance in terms of time and place, and the resulting changes in the course of the history of yemen, as well as in the events of the ottoman- Portuguese conflict on the waters of the Indian ocean.